A non-slip grip material for tampon outer catheter and its preparation method and application

By surface modification of quartz sand, anti-bacterial and anti-slip particles are prepared, and combined with materials such as polyurethane acrylate to form anti-slip handle materials, which solves the problem of the lack of anti-slip and anti-bacterial properties of existing tampon outer catheter handle materials. Achieving higher safety and comfort of use.

CN118421188BActive Publication Date: 2025-01-24YOULIMEI (HUBEI) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410655454.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-01-24
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The grip material of the existing tampon outer catheter lacks anti-slip and antibacterial properties, resulting in inconvenience in use and risk of infection.

Method used

Through the surface modification of quartz sand, introduce antibacterial agents and skin -friendly modifiers, prepare antibacterial non -slip particles, and combine with polyurethane acrylate and other materials to form a non -slip grip material.

Benefits of technology

The anti-slip and antibacterial properties of the handle are improved, and the safety and comfort of the tampon are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004857725890000111
    Figure BDA0004857725890000111
  • Figure BDA0004857725890000121
    Figure BDA0004857725890000121
Patent Text Reader

Abstract

The present invention discloses an anti-skid handle material for the outer catheter of a tampon, and a preparation method and application thereof, comprising the following steps: S1, preparation of composite quartz sand; S2, preparation of modified quartz sand; S3, preparation of antibacterial anti-skid particles; S4, preparation of anti-skid handle material. The anti-skid handle material for the outer catheter of a tampon, the quartz sand itself used can be used as anti-skid particles, the optimal particle size range of the quartz sand is between 150-300 μm, and the anti-skid particles are modified by a specific method so that the anti-skid particles have good anti-skid performance, and then the anti-skid handle material is applied to the handle of the outer catheter of the tampon by spraying, which significantly improves the friction coefficient at the handle, and the introduction of chitosan can not only ensure that the anti-skid particles have good anti-skid performance, but also reduce the particle foreign body sensation generated at the handle, thereby improving the safety and use performance of the tampon, and having good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tampons, and in particular relates to an anti-slip handle material for an outer catheter of a tampon, and a preparation method and application thereof. Background Art

[0002] Tampons, also known as sanitary plugs, can be inserted into the vagina to absorb menstrual blood. Tampons are a cotton cylinder, mainly made of cotton, synthetic fibers or a mixture of these two materials, with diameters ranging from 1 cm to 1.9 cm, with a cotton thread (drawstring) attached to the end. The degree of arc at the tip of the tampon varies from brand to brand, allowing users to choose according to their own usage habits.

[0003] Conventional tampons usually include two inner and outer tubes. The outer tube is generally used to store the tampon, and the inner tube is generally used to push it. One end of the outer tube is provided with a petal-shaped opening, and the other end is fixedly connected to a handle. When using it, pinch the outer side of the handle with your fingers, insert the outer tube into the vagina until the fingers on the outer side of the handle reach the vaginal opening, and then press the inner rod inward to push the tampon body into the vagina.

[0004] However, the existing external catheter handles are basically made of plastic, and their surfaces are relatively smooth and do not have anti-slip properties. When using, some women may have cosmetics or other skin care products on their hands, which leads to insufficient friction between the handle and the fingers, making it easy to slip and inconvenient to use. In the prior art, there are protrusions added to the handle, such as spaced annular protrusions or protrusions distributed in scattered points, to increase the friction between the handle and the fingers, but these are all ways to increase the anti-slip function by changing the structure, and the material properties of the handle itself have not changed, that is, the friction coefficient remains unchanged, and its anti-slip effect is limited and it is not skin-friendly. At the same time, due to the lack of antibacterial properties, some women are worried that bacteria will be introduced into the uterus and cause infection, which increases the chance of infection. Therefore, the art needs to develop a handle material with antibacterial and anti-slip functions. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a non-slip handle material for a tampon outer catheter and a preparation method and application thereof. The handle material has good non-slip properties and also has good antibacterial properties, thereby improving the performance of the tampon and having good application prospects.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0008] S1. Preparation of composite quartz sand: quartz sand is added to a nitric acid solution for immersion, filtered, dried, and then added to an isopropanol aqueous solution, followed by addition of tetrabutyl titanate and ethylenediamine to carry out a hydrothermal reaction. After the reaction is completed, the quartz sand is filtered, washed, and dried to obtain composite quartz sand;

[0009] S2, preparation of modified quartz sand: adding the composite quartz sand in step S1 to an ethanol aqueous solution, then adding 3-chloropropyltriethoxysilane, stirring for reaction, filtering, washing, and drying after the reaction is completed to obtain a solid product; adding the solid product to DMF, then adding 5-guanidine valeric acid, and reacting at a constant temperature under a nitrogen atmosphere, adding triethylamine during the reaction to maintain the pH at 7, and centrifuging, filtering, washing, and drying after the reaction is completed to obtain modified quartz sand;

[0010] S3, preparation of antibacterial and anti-skid particles: adding the modified quartz sand in step S2 to a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stirring and activating, adding chitosan acetic acid solution and N-hydroxysuccinimide, heating and reacting, filtering, washing, drying and grinding after the reaction is completed to obtain antibacterial and anti-skid particles;

[0011] S4. Preparation of anti-skid handle material: under light-proof conditions, add the antibacterial and anti-skid particles, polyurethane acrylate, isopropyl alcohol, polyvinyl pyrrolidone, polyacrylamide and benzophenone in step S3 into a reaction kettle and stir evenly to obtain the anti-skid handle material for the outer catheter of the tampon.

[0012] Preferably, in step S1, the particle size of the quartz sand is 150-300 μm, the mass concentration of the nitric acid is 5-10%, the immersion temperature is 20-30° C., and the immersion time is 20-30 min.

[0013] In the present invention, quartz sand is used as the anti-slip particles, and the surface of the quartz sand is modified to improve the antibacterial property and skin affinity of the quartz sand, thereby ensuring the comfort of the handle material.

[0014] Preferably, the mass fraction of isopropanol in the isopropanol aqueous solution in step S1 is 60-70%, the mass ratio of quartz sand, tetrabutyl titanate and ethylenediamine is 100:60-90:80-100, the temperature of the hydrothermal reaction is 120-150° C., and the time is 7-10 h.

[0015] In the present invention, titanium dioxide is generated in situ on the surface of quartz sand. Titanium dioxide itself has good antibacterial properties, which can improve the antibacterial properties of quartz sand.

[0016] Preferably, the mass fraction of ethanol in the ethanol aqueous solution in step S2 is 50-60%; the mass ratio of the composite quartz sand, the ethanol aqueous solution and 3-chloropropyltriethoxysilane is 100:800-1000:10-20; the temperature of the stirring reaction is 60-70°C and the time is 3-5h.

[0017] Preferably, the mass ratio of the solid product, DMF and 5-guanidine valeric acid in step S2 is 100:1000-1500:7-13; the temperature of the isothermal reaction is 110-120° C., and the time is 6-9 h.

[0018] In the present invention, 5-guanidine valeric acid is introduced into the anti-slip particles in the form of a chemical bond. The guanidine group contained in 5-guanidine valeric acid has good antibacterial properties, which can further improve the antibacterial properties of the anti-slip particles. At the same time, the carboxyl group contained in it is also conducive to the next reaction.

[0019] Preferably, the mass fraction of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution in step S3 is 10-15%; the mass ratio of the modified quartz sand, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, chitosan acetic acid solution, and N-hydroxysuccinimide is 100:1000-1500:200-300:60-90.

[0020] Preferably, the temperature of the heating reaction in step S3 is 80-90° C. and the time is 5-7 hours. The preparation method of the chitosan acetic acid solution is as follows: add 5 g of chitosan to 100 mL of 5% acetic acid solution by mass, stir and dissolve, and obtain the chitosan solution.

[0021] In the present invention, by introducing chitosan into the modified quartz sand, the skin affinity of the quartz sand can be improved, and at the same time, since chitosan itself has antibacterial properties, the antibacterial performance of the quartz sand can be further improved.

[0022] Preferably, the mass ratio of the antibacterial and anti-slip particles, polyurethane acrylate, isopropyl alcohol, polyvinyl pyrrolidone, polyacrylamide, and benzophenone in step S4 is 20-30:60-70:40-50:5-10:3-6:0.2-0.5.

[0023] The present invention also protects an anti-slip handle material for the outer catheter of a tampon prepared by the method as described above.

[0024] The present invention also protects the use of the above-mentioned non-slip handle material for tampon outer catheter on the tampon outer catheter, wherein the non-slip handle material is applied to the handle of the tampon outer catheter by spraying, and then dried and cured by ultraviolet light.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The anti-skid grip material for the outer catheter of a tampon provided by the present invention can be used as anti-skid particles by itself, but its surface is hard and its compatibility with the organic coating polyurethane acrylate is poor, resulting in the anti-skid coating not having a skin-friendly feel. The quartz sand is modified by a specific method to obtain antibacterial and anti-skid particles. The optimal particle size range of the quartz sand is between 150-300 μm. If the particle size range of the quartz sand is greater than 300 μm, it will cause a particle foreign body feeling at the fingers and the grip during use. If the particle size range of the quartz sand is less than 150 μm, it will not work. The quartz sand has an anti-slip effect, so the particle size range of the quartz sand can not only ensure that the anti-slip particles have good anti-slip properties, but also reduce the foreign body sensation of the particles produced at the handle. It is then mixed with UV-curing coating polyurethane acrylate to obtain an anti-slip handle material for the outer catheter of the tampon. The anti-slip handle material is coated on the handle of the outer catheter of the tampon by spraying, and then UV-cured, so that the handle has good anti-slip and antibacterial properties, which greatly improves the safety and performance of the tampon and has good application prospects.

[0027] (2) The anti-slip handle material for the outer catheter of a tampon provided by the present invention has antibacterial and anti-slip particles added thereto. Quartz sand is used as a raw material. The quartz sand surface is first treated with nitric acid to remove impurities and increase the specific surface area of ​​the quartz sand. The quartz sand is then subjected to a hydrothermal reaction with tetrabutyl titanate and ethylenediamine. Titanium dioxide is generated on the surface of the quartz sand by an in-situ synthesis method to improve the antibacterial properties of the quartz sand. Compared with direct mixing, the in-situ synthesis method improves the dispersibility of titanium dioxide. The composite quartz sand is then reacted with 3-chloropropyltriethoxysilane to introduce chlorine-containing groups onto the surface of the composite quartz sand, which is beneficial to the next step of the reaction. The solid product is then reacted with 5-guanidine The modified quartz sand is reacted with valeric acid to introduce guanidine and carboxyl groups on the surface of the composite quartz sand. The guanidine group has good antibacterial properties and can further improve the antibacterial properties of the quartz sand. The introduction of the guanidine group into the surface of the quartz sand by chemical bonds can improve its antibacterial durability. At the same time, the introduced carboxyl group is also beneficial to the next reaction. Finally, the modified quartz sand is reacted with chitosan. Through the amidation reaction of the carboxyl group and the amino group, the chitosan is introduced into the quartz sand by chemical grafting. On the one hand, chitosan has good antibacterial properties and can significantly improve the antibacterial effect of the antibacterial and anti-slip particles. On the other hand, chitosan has good biocompatibility and can improve the skin-friendliness of the handle and improve the comfort of the user. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the present invention, the quartz sand was purchased from Foshan Jinlinda Chemical Co., Ltd., with a particle size of 150-300 μm; the polyurethane acrylate was purchased from Kandis Chemical (Hubei) Co., Ltd.; and the chitosan was purchased from Shandong Guante Bioengineering Co., Ltd.

[0030] Example 1

[0031] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0032] S1. Preparation of composite quartz sand: 100 g of quartz sand was added to 700 g of 10% nitric acid solution, immersed at 25° C. for 25 min, filtered, dried, and then added to 1200 g of isopropanol aqueous solution (the mass fraction of isopropanol was 65%), followed by 80 g of tetrabutyl titanate and 90 g of ethylenediamine, and hydrothermally reacted at 140° C. for 8 h. After the reaction was completed, filtered, washed, and dried to obtain composite quartz sand;

[0033] S2, preparation of modified quartz sand: add 100g of the composite quartz sand in step S1 to 900g of ethanol aqueous solution with a mass fraction of 55%, then add 15g of 3-chloropropyltriethoxysilane, stir and react at 65°C for 4h, filter, wash and dry after the reaction is completed to obtain a solid product; add 100g of the solid product to 1300g of DMF, then add 10g of 5-guanidine valeric acid, react at a constant temperature of 115°C for 8h under a nitrogen atmosphere, add triethylamine during the reaction to keep the pH at 7, centrifuge, filter, wash and dry after the reaction is completed to obtain modified quartz sand;

[0034] S3, preparation of antibacterial and anti-skid particles: add 100g of modified quartz sand in step S2 to 1300g of 15% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stir and activate at 40°C for 1h, add 250g of chitosan acetic acid solution and 80g of N-hydroxysuccinimide, react at 85°C for 6h, filter, wash, dry and grind after the reaction to obtain antibacterial and anti-skid particles; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of 5% acetic acid solution, stir and dissolve to obtain;

[0035] S4, preparation of handle material: under light-proof conditions, add 25g of antibacterial and anti-skid particles, 65g of polyurethane acrylate, 45g of isopropyl alcohol, 8g of polyvinyl pyrrolidone, 5g of polyacrylamide, and 0.4g of benzophenone in step S3 into a reaction kettle, stir evenly, and obtain the anti-skid handle material for the outer catheter of the tampon.

[0036] Example 2

[0037] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0038] S1. Preparation of composite quartz sand: 100 g of quartz sand was added to 700 g of 5% nitric acid solution, immersed at 25° C. for 25 min, filtered, dried, and then added to 1200 g of isopropanol aqueous solution (the mass fraction of isopropanol was 65%), followed by adding 70 g of tetrabutyl titanate and 90 g of ethylenediamine, and hydrothermally reacted at 130° C. for 8 h. After the reaction was completed, filtered, washed, and dried to obtain composite quartz sand;

[0039] S2, preparation of modified quartz sand: add 100g of the composite quartz sand in step S1 to 900g of ethanol aqueous solution with a mass fraction of 55%, then add 15g of 3-chloropropyltriethoxysilane, stir and react at 65°C for 4h, filter, wash and dry after the reaction is completed to obtain a solid product; add 100g of the solid product to 1300g of DMF, then add 10g of 5-guanidine valeric acid, react at a constant temperature of 115°C for 7h under a nitrogen atmosphere, add triethylamine during the reaction to keep the pH at 7, centrifuge, filter, wash and dry after the reaction is completed to obtain modified quartz sand;

[0040] S3, preparation of antibacterial and anti-skid particles: add 100g of modified quartz sand in step S2 to 1300g of 10% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stir and activate at 40°C for 1h, add 250g of chitosan acetic acid solution and 70g of N-hydroxysuccinimide, react at 85°C for 6h, filter, wash, dry and grind after the reaction to obtain antibacterial and anti-skid particles; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of 5% acetic acid solution, stir and dissolve to obtain;

[0041] S4, preparation of handle material: under light-proof conditions, add 25g of antibacterial and anti-skid particles, 65g of polyurethane acrylate, 45g of isopropyl alcohol, 7g of polyvinyl pyrrolidone, 4g of polyacrylamide, and 0.3g of benzophenone in step S3 into a reaction kettle, stir evenly, and obtain the anti-skid handle material for the outer catheter of the tampon.

[0042] Example 3

[0043] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0044] S1. Preparation of composite quartz sand: 100 g of quartz sand was added to 700 g of 5% nitric acid solution, immersed at 20° C. for 30 min, filtered, dried, and then added to 1200 g of isopropanol aqueous solution (the mass fraction of isopropanol was 60%), followed by adding 60 g of tetrabutyl titanate and 80 g of ethylenediamine, and hydrothermally reacted at 120° C. for 10 h. After the reaction was completed, filtered, washed, and dried to obtain composite quartz sand;

[0045] S2, preparation of modified quartz sand: add 100g of the composite quartz sand in step S1 to 800g of 50% ethanol aqueous solution, then add 10g of 3-chloropropyltriethoxysilane, stir and react at 60°C for 5h, filter, wash and dry after the reaction is completed to obtain a solid product; add 100g of the solid product to 1000g of DMF, then add 7g of 5-guanidine valeric acid, and react at a constant temperature of 110°C for 9h under a nitrogen atmosphere. During the reaction, add triethylamine to keep the pH at 7. After the reaction is completed, centrifuge, filter, wash and dry to obtain modified quartz sand;

[0046] S3, preparation of antibacterial and anti-skid particles: add 100g of modified quartz sand in step S2 to 1000g of 15% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stir and activate at 40°C for 1h, add 200g of chitosan acetic acid solution and 60g of N-hydroxysuccinimide, react at 80°C for 7h, filter, wash, dry and grind after the reaction to obtain antibacterial and anti-skid particles; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of 5% acetic acid solution, stir and dissolve to obtain;

[0047] S4, preparation of handle material: under light-proof conditions, add 20g of antibacterial and anti-skid particles, 60g of polyurethane acrylate, 40g of isopropyl alcohol, 5g of polyvinyl pyrrolidone, 3g of polyacrylamide, and 0.2g of benzophenone in step S3 into a reaction kettle, stir evenly, and obtain the anti-skid handle material for the outer catheter of the tampon.

[0048] Example 4

[0049] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0050] S1. Preparation of composite quartz sand: 100 g of quartz sand was added to 700 g of 10% nitric acid solution, immersed at 30° C. for 20 min, filtered, dried, and then added to 1200 g of isopropanol aqueous solution (the mass fraction of isopropanol was 70%), followed by adding 90 g of tetrabutyl titanate and 100 g of ethylenediamine, and hydrothermally reacted at 150° C. for 7 h. After the reaction was completed, filtered, washed, and dried to obtain composite quartz sand;

[0051] S2, preparation of modified quartz sand: add 100g of the composite quartz sand in step S1 to 1000g of 60% ethanol aqueous solution, then add 20g of 3-chloropropyltriethoxysilane, stir and react at 70°C for 3h, filter, wash and dry after the reaction is completed to obtain a solid product; add 100g of the solid product to 1500g of DMF, then add 13g of 5-guanidine valeric acid, react at a constant temperature of 120°C for 6h under a nitrogen atmosphere, add triethylamine during the reaction to keep the pH at 7, centrifuge, filter, wash and dry after the reaction is completed to obtain modified quartz sand;

[0052] S3, preparation of antibacterial and anti-skid particles: add 100g of modified quartz sand in step S2 to 1500g of 10% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stir and activate at 40°C for 1h, add 300g of chitosan acetic acid solution and 90g of N-hydroxysuccinimide, react at 90°C for 5h, filter, wash, dry and grind after the reaction to obtain antibacterial and anti-skid particles; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of 5% acetic acid solution, stir and dissolve to obtain;

[0053] S4, preparation of handle material: under light-proof conditions, add 30g of antibacterial and anti-skid particles, 70g of polyurethane acrylate, 50g of isopropyl alcohol, 10g of polyvinyl pyrrolidone, 6g of polyacrylamide, and 0.5g of benzophenone in step S3 into a reaction kettle, stir evenly, and obtain the anti-skid handle material for the outer catheter of the tampon.

[0054] Comparative Example 1

[0055] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0056] S1. Preparation of composite quartz sand: 100 g of quartz sand was added to 700 g of 10% nitric acid solution, immersed at 25° C. for 25 min, filtered, dried, and then added to 1200 g of isopropanol aqueous solution (the mass fraction of isopropanol was 65%), followed by 80 g of tetrabutyl titanate and 90 g of ethylenediamine, and hydrothermally reacted at 140° C. for 8 h. After the reaction was completed, filtered, washed, and dried to obtain composite quartz sand;

[0057] S2, preparation of antibacterial and anti-skid particles: add 100g of the composite quartz sand in step S1 to 1300g of 15% 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stir and activate at 40°C for 1h, add 250g of chitosan acetic acid solution and 80g of N-hydroxysuccinimide, react at 85°C for 6h, filter, wash, dry and grind after the reaction to obtain antibacterial and anti-skid particles; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of 5% acetic acid solution, stir and dissolve to obtain;

[0058] S4, preparation of handle material: under light-proof conditions, add 25g of antibacterial and anti-skid particles, 65g of polyurethane acrylate, 45g of isopropyl alcohol, 8g of polyvinyl pyrrolidone, 5g of polyacrylamide, and 0.4g of benzophenone in step S3 into a reaction kettle, stir evenly, and obtain the anti-skid handle material for the outer catheter of the tampon.

[0059] Comparative Example 2

[0060] A method for preparing a non-slip handle material for a tampon outer catheter comprises the following steps:

[0061] S1. Preparation of modified quartz sand: 100 g of quartz sand was added to 900 g of ethanol aqueous solution with a mass fraction of 55%, and then 15 g of 3-chloropropyltriethoxysilane was added, and the mixture was stirred at 65° C. for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product; 100 g of the solid product was added to 1300 g of DMF, and then 10 g of 5-guanidine valeric acid was added, and the mixture was kept at a constant temperature of 115° C. for 8 h under a nitrogen atmosphere. During the reaction, triethylamine was added to maintain the pH at 7. After the reaction was completed, the mixture was centrifuged, filtered, washed, and dried to obtain modified quartz sand;

[0062] S2. Preparation of handle material: under light-proof conditions, add 25 g of modified quartz sand, 65 g of polyurethane acrylate, 45 g of isopropyl alcohol, 8 g of polyvinyl pyrrolidone, 5 g of polyacrylamide, and 0.4 g of benzophenone in step S3 into a reactor and stir evenly to obtain the anti-slip handle material for the outer catheter of the tampon.

[0063] The anti-slip handle material for the tampon outer catheter prepared in Examples 1-4 and Comparative Examples 1-2 was applied to the tampon outer catheter, specifically as follows: the anti-slip handle material was applied to the handle of the tampon outer catheter by spraying, the coating thickness was controlled to be 100 μm, dried at 80° C. for 4 h, and heated at 150 mW / cm 2UV curing for 2 minutes at a power of , and then washing with deionized water to obtain the sample product. Then, referring to the YY0325-2016 standard and the "Technical Specifications for Disinfection", the antibacterial ring test method was used to test the antibacterial properties of the above sample products. Staphylococcus aureus (ATCC25923) and Escherichia coli (ATCC25922) were used as test strains. The incubator temperature was 40°C, the humidity was 60%, and the culture cycle was 1d, 3d and 5d. The specific test data are shown in Table 1:

[0064] Table 1

[0065]

[0066]

[0067] It can be seen from the data in Table 1 that the anti-slip handle material for the outer catheter of a tampon prepared in the present invention has a good antibacterial effect.

[0068] The tampon outer catheter non-slip handle material prepared in Example 1 and Comparative Examples 1-2 was sprayed on a polypropylene plastic plate, the coating thickness was controlled to be 100 μm, and dried at 80° C. for 4 h. 2 UV curing for 2 minutes at a power of , then washing with deionized water to obtain a sample, and the sample was subjected to a friction coefficient test. The friction coefficient test: the sample was immersed in water for 30 seconds, then fixed on the groove plate, and water was injected into the water tank until the sample was completely immersed in it. A 200g standard slider was gently placed on top of the sample, and the slider was dragged by the sensor connecting rod to move at a speed of 100mm / min to measure the dynamic friction coefficient. The specific test data are shown in Table 2:

[0069] Table 2

[0070] Example 1 Comparative Example 1 Comparative Example 2 Friction coefficient 0.93 0.91 0.82 Hand feel evaluation Skin-friendly Skin-friendly Ice hard feeling

[0071] It can be seen from the friction coefficient data in Table 2 that the anti-slip handle material for the outer catheter of the tampon prepared by the present invention has a higher friction coefficient, which can increase the friction between the fingers and the handle, is not easy to slip during use, and improves the performance of the tampon. It also has a good skin-friendly feel and has good application prospects.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a non-slip handle material for a tampon outer catheter, characterized in that: The following steps are involved: S1. Preparation of composite quartz sand: quartz sand is added to a nitric acid solution for immersion, filtered, dried, and then added to an isopropanol aqueous solution, followed by addition of tetrabutyl titanate and ethylenediamine to carry out a hydrothermal reaction. After the reaction is completed, the quartz sand is filtered, washed, and dried to obtain composite quartz sand; S2, preparation of modified quartz sand: adding the composite quartz sand in step S1 to an ethanol aqueous solution, then adding 3-chloropropyltriethoxysilane, stirring for reaction, filtering, washing, and drying after the reaction is completed to obtain a solid product; adding the solid product to DMF, then adding 5-guanidine valeric acid, and reacting at a constant temperature under a nitrogen atmosphere, adding triethylamine during the reaction to maintain the pH at 7, and centrifuging, filtering, washing, and drying after the reaction is completed to obtain modified quartz sand; S3, preparation of antibacterial and anti-skid particles: adding the modified quartz sand in step S2 to a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, stirring and activating, adding chitosan acetic acid solution and N-hydroxysuccinimide, heating and reacting, filtering, washing, drying and grinding after the reaction is completed to obtain antibacterial and anti-skid particles; S4, preparation of anti-skid handle material: under light-proof conditions, add the antibacterial anti-skid particles, polyurethane acrylate, isopropyl alcohol, polyvinyl pyrrolidone, polyacrylamide, and benzophenone in step S3 into a reaction kettle, and stir evenly to obtain the anti-skid handle material for the outer catheter of the tampon; The particle size of the quartz sand in step S1 is 150-300 μm, and the mass ratio of the quartz sand, tetrabutyl titanate, and ethylenediamine is 100:60-90:80-100; the mass ratio of the composite quartz sand, ethanol aqueous solution, and 3-chloropropyltriethoxysilane in step S2 is 100:800-1000:10-20, and the mass ratio of the solid product, DMF, and 5-guanidine valeric acid is 100:1000-1500:7-13; the mass fraction of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution in step S3 is 10-15%, and the modified quartz sand, 1 The mass ratio of -(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution, chitosan acetic acid solution, and N-hydroxysuccinimide is 100:1000-1500:200-300:60-90; the preparation method of the chitosan acetic acid solution is as follows: add 5g of chitosan to 100mL of acetic acid solution with a mass fraction of 5%, stir and dissolve, and obtain; the mass ratio of the antibacterial and anti-slip particles, polyurethane acrylate, isopropanol, polyvinyl pyrrolidone, polyacrylamide, and benzophenone in step S4 is 20-30:60-70:40-50:5-10:3-6:0.2-0.

5.

2. The preparation method according to claim 1, characterized in that: The mass concentration of the nitric acid in step S1 is 5-10%, the immersion temperature is 20-30° C., and the immersion time is 20-30 min.

3. The preparation method according to claim 1, characterized in that: The mass fraction of isopropanol in the isopropanol aqueous solution in step S1 is 60-70%, the temperature of the hydrothermal reaction is 120-150° C., and the time is 7-10 hours.

4. The preparation method according to claim 1, characterized in that: The mass fraction of ethanol in the ethanol aqueous solution in step S2 is 50-60%; the temperature of the stirring reaction is 60-70° C. and the time is 3-5 hours.

5. The preparation method according to claim 1, characterized in that: The isothermal reaction in step S2 is carried out at a temperature of 110-120° C. and for a time of 6-9 hours.

6. The preparation method according to claim 1, characterized in that: The heating reaction temperature in step S3 is 80-90° C. and the time is 5-7 h.

7. An anti-slip handle material for a tampon outer catheter prepared by the method according to any one of claims 1 to 6.

8. An application of the anti-slip grip material for a tampon outer catheter as claimed in claim 7 on a tampon outer catheter, characterized in that: The anti-slip handle material is applied to the handle of the outer catheter of the tampon by spraying, and then cured by ultraviolet light after drying.

Citation Information

Patent Citations

  • Preparation method of highly antistatic antiskid floor paint

    CN107629628A

  • Antibacterial coating for surface layer of medical equipment and preparation method of antibacterial coating

    CN108410317A